POMONA: a multiplatform software for modeling seed physiology - Cantão, Renato Fernandes; Ribeiro-Oliveira, João Paulo; Silva, Edvaldo A. Amaral da [UNESP]; Santos, Amanda Rithieli dos [UNESP]; de Faria, Rute Quelvia [UNESP]; Sartori, Maria Marcia Pereira [UNESP] (Frontiers, 2023)
Seed physiology is related to functional and metabolic traits of the seed-seedling transition. In this sense, modeling the kinetics, uniformity and capacity of a seed sample plays a central role in designing strategies for trade, food, and environmental security. Thus, POMONA is presented as an easy-to-use multiplatform software designed to bring several logistic and linearized models into a single package, allowing for convenient and fast assessment of seed germination and or longevity, even if the data has a non-Normal distribution. POMONA is implemented in JavaScript using the Quasar framework and can run in the Microsoft Windows operating system, GNU/Linux, and Android-powered mobile hardware or on a web server as a service. The capabilities of POMONA are showcased through a series of examples with diaspores of corn and soybean, evidencing its robustness, accuracy, and performance. POMONA can be the first step for the creation of an automatic multiplatform that will benefit laboratory users, including those focused on image analysis.
Keywords: agriculture 5.0; algebraic models; automated scoring; corn; plant physiology; seed quality; soybean